The labiate family in the Malaspina expedition (1789-1794). I - Fernández-Alonso, José Luis; Morales, Ramón (Botanica Complutensis, 2013)
The sheets of Lamiaceae deposited in the herbarium MA collected by Luis Neé during the Malaspina expedition, that in 5 years traveled along America, Philippines, Australia, and some Pacific islands. They were studied and identified 166 sheets corresponding to 68 species and 23 genera of the Lamiaceae family. The most of the identified collections (14 genera and 51 species) are from América. New type material has been located of two species of Gardoquia. In a subsequent independent work the genus Salvia (another 164 sheets corresponding to 46 species) will be published.